Textbook of medical physiology - Guyton, Arthur C. 4 0 16; (John Edward), 1946- Hall, John E.; 5 (Philadelphia : W.B. Saunders, 1996)
A textbook of medical physiology, featuring over eighty chapters grouped in fifteen units, covering the heart, circulation, the kidneys and body fluids, respiration, and other body systems; and including discussion of sports physiology.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Human physiology.;Physiology, Pathological.;Physiology.;Physiology.; 20; 2